KEMAMPUAN PEGAWAI BUMDES DALAM MENGAPLIKASIKAN ZAHIR DALAM PEMBUATAN LAPORAN KEUANGAN DI DESA PEMATANG SERAI TANJUNG PURA DI SUMATERA UTARA - Vina Arnita; Hernawaty Hernawaty; Eky Ermal M (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
In this dedication the researcher helps provide solutions to Bumdes employees to make financial reports. At the beginning of this dedication, the researchers visited Pematang Village, Lemongrass, Tanjung Pura, and Bumdes employees told of their strengths and weaknesses. The deficiencies faced by them were also explained during the visit. The village residents who were in the area of Lemongrass Temple were one of the villages that received grants from the central government. So the problems that arise they do not understand to make computerized financial statements. With this problem the researchers took part in alleviating their problems in making financial statements. The disadvantage faced by them was that the employees in Bumdes only graduated from high school, so they did not know how to make a correct financial report. Educational background for Bumdes employees makes it difficult for them to understand financial statements, researchers provide learning about accounting and accounts from accounting. After they understand new accounts entered into journals. By completing accounts and journals, then they can enter financial reports through the zahir application.